Intensivvårdssjuksköterskans mätning av gastrisk residualvolym hos patienter med enteral nutrition - Källman,Beatrice; Adamczewski,Malgorzata (2022)
Background: Checking gastric residual volumes (GRV) by aspiration is a method practiced on intensive care units with the purpose of lowering the risk of complications due to enteral nutrition (EN) as well as to ensure adequate delivery of EN. Studies have shown disagreement whether large GRVs increase the risk of negative effects, also the methods of measuring vary by technique, frequency and amount aspirated. Routines vary across intensive care units in Sweden and measuring GRV is not recommended by international guidelines. Aim: The aim of this study was to examine if the intensive care nurse’s routinely measuring of GRVs on patients with enteral nutrition (EN) was motivated and if it could be associated with negative effects. Methods: Literature review with systematic approach based on the results of 14 scientific articles of quantitative methods analyzed with narrative synthesis. Results: Five main themes were identified after synthesis of the results: routinely measuring GRV not motivated; routinely measuring GRV motivated; nutritional supply; gastrointestinal (GI) intolerance; and negative effects in the context of GRV routines. Twelve of the articles stated that routinely measuring GRVs was not motivated. Further stated was that eliminating GRV measures could contribute to increased nutritional supplies, but no difference was found between GI intolerance and other negative effects. Summary: The total results agree with previous studies and indicate that there are no benefits to routinely measure GRVs. More randomized controlled trials are needed, as well as a united definition of the term GI intolerance. Eliminating GRV measures could lead to increased feedings of EN without affecting the presence of GI intolerance or negative effects. EN and its supply is key in improving the patient’s health and lowering negative effects associated with intensive care. The intensive care nurse therefore must make an individual evaluation carrying a person-centered approach in the necessity of and relevance in measuring GRVs.
Keywords: Gastrisk residualvolym; Enteral nutrition; Intensivvård; Mekanisk ventilation; Nutritionssond.